2016
DOI: 10.17159/2309-8775/2016/v58n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration of concrete construction induced by acid mine drainage attack

Abstract: This paper presents findings from microanalytical investigation conducted on disintegrated concrete that had been used to construct a weir within a coal mine in South Africa. The concrete was in contact with polluted mine water, commonly referred to as acid mine drainage (AMD). Accordingly, the weir had been exposed to AMD decant which led to disintegration of concrete due to chemical attack. Investigations were conducted by optical microscopy (OM), scanning electron microscopy (SEM) equipped with energy dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Various recent studies [1]- [3] have shown pervious concrete to be an effective medium for treatment of acid mine drainage (AMD). This material is made by mixing single-size coarse aggregate with Portland cement and water to produce highly porous concrete.…”
Section: A Pervious Concrete In Column Experimentsmentioning
confidence: 99%
“…Various recent studies [1]- [3] have shown pervious concrete to be an effective medium for treatment of acid mine drainage (AMD). This material is made by mixing single-size coarse aggregate with Portland cement and water to produce highly porous concrete.…”
Section: A Pervious Concrete In Column Experimentsmentioning
confidence: 99%
“…The commonly used test procedure of assessment is to immerse concrete samples in an acid solution (known as the immersion method), which directly investigates the resistance of concrete to acid. Many researchers [48,51,[76][77][78][79][80][81][82] have used this method to evaluate the effectiveness of supplementary cementitious materials (SCMs) in improving the acid resistance of the concrete. However, there are many drawbacks regarding the immersion method.…”
Section: Cement-based Rehabilitation-materials Selection Based On the mentioning
confidence: 99%
“…Due to its distinctive bright colours, AMD alters the environmental aesthetic, causes habitat alteration and disruption of the nutrient cycle [10]. Moreover, due to its acidity, AMD induces corroding effects on infrastructure such as bridges and sculptures and contributes to the deterioration of roads around the impacted areas [11]. Additional impacts include the loss of biodiversity and decline of aquatic ecosystems [12].…”
Section: Introductionmentioning
confidence: 99%